Disrupting the Center : A Partnership Approach to Writing Across the University - Hallman Martini, Rebecca (Book collections on Project MUSE., 2021)
"Analyzes and critiques one particular writing center's partnership-approach to collaboration with disciplinary faculty and upper administrators across the curriculum and offers writing centers a framework for responding to disruptive innovations in higher education"--